The role of management in the evaluation and teaching organization - Ignasi Llompart Mas; Carles Mata; Josep María Pérez (ADIDE Federación, 2007)
The mayor purpose of every kind of schools' performance evaluation is to favour innovation, change and improvement. Are schools capable of undertaking changes? If so, these changes can only occur under the guidance and leadership of the school Principal, whose School Management Programme constitutes a key element in the process. It is also necessary a change in the hierarchical dependence of schools from the Educational Authorities, which implies a new framework civil service in educational grounds and the wider development of an scheduled career for teachers in the civil service.